Students' motivating influences for selecting dental hygiene and a 4‐year degree: A retrospective study. - Katyal, Shivalika; Kanji, Zul (International Journal of Dental Hygiene, 2021)
Purpose: A growing body of research is exploring why applicants select to enrol into a 4‐year dental hygiene degree in Canada when the entry‐to‐practice credential remains a diploma. The aims of this study were to investigate first‐year entry‐to‐practice students' motivating influences for choosing the dental hygiene profession and enrolling in a baccalaureate program. Methods: Between 2013 and 2018, first‐year students in the University of British Columbia's Bachelor of Dental Science program completed orientation surveys. A secondary data analysis was conducted on a total of 127 orientation surveys from a cumulative first‐year population over a 5‐year period. 159 students participated in the surveys for an 80% response rate. Survey questions were open‐ended. Saldaña's approach to coding was used to analyse the descriptive data for emerging themes. Results: The primary reasons for choosing dental hygiene as a profession included personal desire (65%) which involved students' desire to help others, as well as past experience (32%) relating to personal, goal or external experiences. Two prominent themes for choosing a dental hygiene degree emerged and included expanding career opportunities outside of clinical practice (82%) and broadening and deepening one's knowledge base (34%). Conclusions: The results provide insight about the factors that influence prospective dental hygiene students to pursue a baccalaureate credential that is presently beyond the entry‐to‐practice requirements for the dental hygiene profession in Canada.